Care work : gender, class, and the welfare state - Harrington Meyer, Madonna, 1959- (Routledge, 2000)
This book is a collection of original essays on the meaning of providing care. The main goal of this book is to re-conceive the notion of care work, beginning with replacing the phrase 'caregiver' with the phrase 'care worker'.